DIRECTNESS AND INDIRECTNESS IN ENGLISH AND UZBEK MEDIA DISCOURSE: IMPLICATIONS FOR POLITENESS AND SOCIAL HARMONY - Bekberganov , Avazbek (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This thesis explores the contrasting communicative styles in English and Uzbek media discourse, where English outlets prioritize directness to promote clarity and debate, while Uzbek media employs indirectness to safeguard social harmony and relational politeness. Through a comparative discourse analysis of news articles and broadcasts from sources like BBC and Kun.uz (2023–2025), the study employs qualitative pragmatic frameworks and quantitative content metrics to examine how these strategies influence audience perception and interaction. Findings indicate that directness in English media enhances argumentative engagement but risks confrontation, whereas Uzbek indirectness fosters consensus and cultural cohesion, aligning with high-context norms. The research underscores the need for culturally attuned media practices in globalized contexts, contributing to cross-cultural pragmatics by bridging linguistic theory with media studies.